ETHICAL IMPLICATIONS OF OUTSOURCING AND OFFSHORING IN GLOBAL BUSINESS PRACTICES: IMPACTS ON LOCAL ECONOMIES, LABOR RIGHTS, AND THE ENVIRONMENT [IMPLIKASI ETIS DARI OUTSOURCING DAN OFFSHORING DALAM PRAKTIK BISNIS GLOBAL: DAMPAKNYA TERHADAP EKONOMI LOKAL, HAK PEKERJA, DAN LINGKUNGAN] - Hayatul Khairul Rahmat (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
Outsourcing and offshoring are critical international business strategies for enhancing cost efficiency and expanding global markets. However, these practices carry significant ethical implications, particularly concerning local economies, labor rights, and environmental standards. While offshoring can stimulate economic growth in developing countries by creating jobs and transferring technology, it often results in economic inequality, labor exploitation, and environmental degradation. Additionally, outsourcing frequently involves violations of labor rights, such as low wages and poor working conditions, as well as negative environmental impacts due to weaker regulations in host countries. This study aims to explore the ethical impacts of outsourcing and offshoring, and the role of regulatory mechanisms and ethical guidelines in mitigating the negative effects of these practices.